2016
DOI: 10.1097/brs.0000000000001573
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Postoperative Photographs and Surgical Outcomes of Patients With Kyphosis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This discrepancy was inferred from chronic sustained back pain, caused by malalignment of the thoracolumbar spine (i.e., kyphosis) even with neurological improvement. Although the discrepancy of radiological outcomes and clinical outcomes are often reported by some articles [3,34,41-43], some other evidence also reported that T-L junction kyphosis led to chronic back pain and that its correction resulted in the improvement of clinical symptoms in the posttraumatic kyphosis [7,39,44].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy was inferred from chronic sustained back pain, caused by malalignment of the thoracolumbar spine (i.e., kyphosis) even with neurological improvement. Although the discrepancy of radiological outcomes and clinical outcomes are often reported by some articles [3,34,41-43], some other evidence also reported that T-L junction kyphosis led to chronic back pain and that its correction resulted in the improvement of clinical symptoms in the posttraumatic kyphosis [7,39,44].…”
Section: Discussionmentioning
confidence: 99%
“…40 Our findings of a positive effect of showing pre-and post-TKR standing photographs to patients to improve self-reported outcomes are compatible with previous reports of a positive effect of standing photographs in improving the self-reported outcome scores after surgical treatment of adolescent idiopathic scoliosis and kyphotic spinal deformity patients. 20,21 In these studies, Albayrak et al 21 reported a benefit of showing pre-and postoperative standing photographs in improving the postoperative SF-36 score and Scoliosis Research Society (SRS)-22r survey (domains of pain, self-image, mental health, and satis-faction, as well as total score) among patients who had undergone corrective surgery for a kyphotic deformity. In another study among patients who had undergone corrective surgery for a Lenke type 1 scoliosis, the same authors reported higher SRS-22r scores (domains of self-image, function, activity, and satisfaction) for patients who were shown their photographs, compared with a group for whom photographs were not obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The use of standing photographs, before and after surgery, has been shown to be effective in improving satisfaction and clinical outcome scores in patients treated for adolescent idiopathic scoliosis and kyphotic spinal deformity. 20,21 Therefore, our aim in this study was to evaluate the effectiveness of showing patients standing photographs of themselves, obtained before and after TKR, on postoperative quality of life and clinical outcome scores measured at 6 months post-TKR.…”
mentioning
confidence: 99%
“…Previously conducted studies have shown that adolescents operated for scoliosis 4 and kyphosis 5 improved their satisfaction as measured by Scoliosis Research Society Health-Related Quality of Life Questionnaire (SRS-22) scores after showing them preoperative and postoperative full-spine photographs. The influence of clinical photography in patient satisfaction after adult deformity surgery has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%